Intercomparison of five nets used for mesozooplankton sampling - ALTUKHOV, D.; SIOKOU, I.; PANTAZI, M.; STEFANOVA, K.; TIMOFTE, F.; GUBANOVA, A.; NIKISHINA, A.; ARASHKEVICH, E. (Mediterranean marine science, 2015)
Intercomparison of nets commonly used for mesozooplankton sampling in the Black and Mediterranean seas was attempted within SESAME (Southern European Seas: Assessing and Modelling Ecosystem Changes) project. Five nets were compared: three Juday nets equipped with 150 μm, 180 μm and 200 μm mesh size, Nansen net (100 μm mesh size) and WP2 (200 μm mesh size). Replicated samples were collected at one station in the western Black Sea offshore waters in April 2009. Collected samples were analyzed at species level (except for meroplankton), stages (for copepods) and size length. A decrease of total abundance values was observed with increasing mesh size, due to the significantly higher numbers of animals smaller than 1 mm in the samples obtained by fine mesh size than with coarser nets. Few comparisons were revealed significant for the abundance of animals with 1-2 mm length, while no significance was detected for specimens larger than 2 mm. The above differences resulted in discripancies between nets regarding species and stages composition. Biomass values did not differ significantly between nets, due to the strong contribution to total biomass of the large animals fraction (Calanus euxinus). The smallest and the largest animals revealed high variability between replicates collected by Nansen, Juday- 200 μm and WP2 nets. Correction factors were calculated for the conversion of abundance values between each couple of nets. The detected differences between nets regarding the abundance and biomass, the community taxonomic composition and size structure, as well as the estimated correction factors, provide useful information for the harmonization of data obtained by the above nets in the Black Sea.